Genetic relationship between some Spanish Vitis vinifera L. subsp. sativa cultivars and wild grapevine populations (Vitis vinifera L subesp. silvestris (Gmelin) Hegi): a preliminary study - Carreño, E.=700 1 Lopez, M.A.; Labra, M.; Rivera, D.; Sancha, J.; Ocete, R.; Martinez de Toda, F.
(En, Es, Fr)
ilus., 11 ref.
Keywords: VITIS VINIFERA; VARIACION GENETICA; ITALIA